Shear lag sutures: Improved suture repair through the use of adhesives. (1st September 2015) - Linderman, Stephen W.; Kormpakis, Ioannis; Gelberman, Richard H.; Birman, Victor; Wegst, Ulrike G.K.; Genin, Guy M.; Thomopoulos, Stavros
Graphical abstract: Abstract: Suture materials and surgical knot tying techniques have improved dramatically since their first use over five millennia ago. However, the approach remains limited by the ability of the suture to transfer load to tissue at suture anchor points. Here, we predict that adhesive-coated sutures can improve mechanical load transfer beyond the range of performance of existing suture methods, thereby strengthening repairs and decreasing the risk of failure. The mechanical properties of suitable adhesives were identified using a shear lag model. Examination of the design space for an optimal adhesive demonstrated requirements for strong adhesion and low stiffness to maximize the strength of the adhesive-coated suture repair construct. To experimentally assess the model, we evaluated single strands of sutures coated with highly flexible cyanoacrylates (Loctite 4903 and 4902), cyanoacrylate (Loctite QuickTite Instant Adhesive Gel), rubber cement, rubber/gasket adhesive (1300 Scotch-Weld Neoprene High Performance Rubber & Gasket Adhesive), an albumin-glutaraldehyde adhesive (BioGlue), or poly(dopamine). As a clinically relevant proof-of-concept, cyanoacrylate-coated sutures were then used to perform a clinically relevant flexor digitorum tendon repair in cadaver tissue. The repair performed with adhesive-coated suture had significantly higher strength compared to the standard repair without adhesive. Notably, cyanoacrylate provides strong adhesion with high stiffness and brittle behavior, and is therefore not an ideal adhesive for enhancing suture repair. Nevertheless, the improvement in repair properties in a clinically relevant setting, even using a non-ideal adhesive, demonstrates the potential for the proposed approach to improve outcomes for treatments requiring suture fixation. Further study is necessary to develop a strongly adherent, compliant adhesive within the optimal design space described by the model.